Precise Control of Microcapillary Size in Microcapillary Films by Liquid‐Assisted Extrusion. Issue 7 (22nd April 2022) - Liu, Junfeng; Zheng, Suxia; Bi, Mingcheng; Xu, Zhongbin; Huang, Xing
Abstract: Microcapillary films (MCFs) are plastic films with an array of microcapillaries, which have been widely applied in microfluidics and bioanalytical techniques. However, the precise control of microcapillary size is still a problem hindering the industrial applications of MCFs because the high size uniformity of microcapillaries ensures the production of homogeneous droplets and the robust performance of immunoassays. Here, a novel approach is provided to precisely adjust the size of microcapillaries by liquid‐assisted extrusion and to investigate the combined effects of extrusion, drawing and liquid injection on the microcapillary size. Compared with gas‐assisted extrusion, the size uniformity is improved by at least 5% for 89% experiments and 10% for 42% experiments. Therefore, this method facilitates MCFs' applications in droplet microfluidics and biotechnologies. Abstract : A novel approach to precisely control the microcapillary size by liquid‐assisted extrusion is provided. The effects of extrusion, drawing, and liquid injection on microcapillary size are investigated. The size uniformity is significantly improved than the gas‐assisted extrusion process. Therefore, microcapillary films with high size uniformity can be widely applied in droplet microfluidics and immunoassays.